Teaching Listening By Using Songs to Students of Junior High School - Syarifah Yuanda Azura; Bukhari Daud; Diana Fauzia Sari (Research in English and Education Journal, 2017)
This study aims to find out whether songs to improve students’ listening skill. Song is one of the media which can help students to improve listening skill and easy to increase their vocabulary in answer the exercise with fill in the blank. The sample of this research was class VII which consisted of 20 Students. The researcher used random sampling to choose the sample. This research used one group pre-test and post-test design. it is one of the research designs in experimental research. The pre-test was given before treatments, while post-test was given after students taught treatments using songs. The instruments used in this research were tests; they were pre-test and post-test. Both of pre-test and post-test consisted of ten questions. The technique of data analysis, the researcher used statistical formula. The mean score of pre-test was 42 and the post-test was 75. Furthermore, the result of calculation of the t-test was 11.83, while the critical value of 0.05 level significant was 2.093 and degree of freedom is 19. T-test (11.83) was higher than t-score of the table ((2.093). it concluded that using songs in teaching reading can increase students listening comprehension.